Synthesis, Properties, and Reactions of Vitamin K Analogs - Klemm, Bradley P.; Stromich, Jeremiah J.; Doyle, Philip M.; Tsogtbaatar, Enkhtuul (My University, 2010)
The synthesis of new vitamin K analogs has been undertaken. We have recently reported that two of these compounds act as in vivo adjuvants that enhance anticogulant activity of Warfarin in rats. The prepartation and characterization of these compounds is being continued with the aim to synthesize new oral anticoagulant compounds.
Color poster with text, diagrams, and graphs.
Keywords: Vitamin K--Derivatives; Derivatives (Chemical)--Synthesis; Anticoagulants (Medicine); Posters